2008
DOI: 10.1037/a0012873
|View full text |Cite
|
Sign up to set email alerts
|

The P300 as an electrophysiological probe of alcohol expectancy.

Abstract: Language-based measures indicate that alcohol expectancies influence alcohol consumption. To relate these measures to brain actions that precede verbal output, the P300 component of the Eventrelated potentials (ERPs) was used to detect violations of individually held alcohol expectancies. As predicted, P300 amplitude elicited by negative alcohol expectancy stimuli was positively correlated with endorsement of positive/arousing alcohol expectancies on the language-based measure, such that the higher an individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 114 publications
0
8
0
Order By: Relevance
“…The gender differences in alcohol expectations may play a further role in changing drinking patterns and, although speculative, may reflect influences of some advertisements that promote a sexual and liberating image in association with alcohol consumption. These findings have additional implications in that positive and arousing alcohol expectancies have been associated with a blunted response to negative affect cues and may represent a form of implicit cognition related to biopsychosocial antecedents influencing drinking behavior (Fishman et al, 2008; Drobes et al, 2009). …”
Section: Discussionmentioning
confidence: 88%
“…The gender differences in alcohol expectations may play a further role in changing drinking patterns and, although speculative, may reflect influences of some advertisements that promote a sexual and liberating image in association with alcohol consumption. These findings have additional implications in that positive and arousing alcohol expectancies have been associated with a blunted response to negative affect cues and may represent a form of implicit cognition related to biopsychosocial antecedents influencing drinking behavior (Fishman et al, 2008; Drobes et al, 2009). …”
Section: Discussionmentioning
confidence: 88%
“…Word-based responses come from living humans, and anticipatory neurobiological networks mostly have been accessed with biological probes that could not be used in humans. Some initial probes of this kind have been supportive (e.g., Fishman, Goldman, & Donchin, 2008), but more work needs to be done using other neuroimaging methods. If sufficient correspondence between neurobiological probes and cognitive measurement tools can be demonstrated, we may be able to increase our array of targets for prevention research.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Johnston and Wang (1991) showed that identical pictures elicited different P300 amplitudes in women at different phases of the menstrual cycle, such that pictures of babies and male models evoked larger P300s in women in the high-progesterone phase as compared to women in the low-progesterone phase. Recently, Fishman, Goldman, and Donchin (2008) have demonstrated P300 sensitivity to individual-specific experiences with (and beliefs about the outcomes of) alcohol use by employing experimental stimuli evoking a wide range of consequences of alcohol ingestion. Only those participants who reported frequent consumption of alcohol in large amounts and believed in “positive” effects of alcohol exhibited large P300 when presented with stimuli suggesting opposite (i.e., negative) effects of drinking.…”
Section: Introductionmentioning
confidence: 99%